Intratumor Heterogeneity of the Estrogen Receptor and the Long-term Risk of Fatal Breast Cancer. (19th January 2018) - Lindström, Linda S; Yau, Christina; Czene, Kamila; Thompson, Carlie K; Hoadley, Katherine A; van't Veer, Laura J; Balassanian, Ron; Bishop, John W; Carpenter, Philip M; Chen, Yunn-Yi; Datnow, Brian; Hasteh, Farnaz; et al.
Abstract: Background: Breast cancer patients with estrogen receptor (ER)–positive disease have a continuous long-term risk for fatal breast cancer, but the biological factors influencing this risk are unknown. We aimed to determine whether high intratumor heterogeneity of ER predicts an increased long-term risk (25 years) of fatal breast cancer. Methods: The STO-3 trial enrolled 1780 postmenopausal lymph node–negative breast cancer patients randomly assigned to receive adjuvant tamoxifen vs not. The fraction of cancer cells for each ER intensity level was scored by breast cancer pathologists, and intratumor heterogeneity of ER was calculated using Rao's quadratic entropy and categorized into high and low heterogeneity using a predefined cutoff at the second tertile (67%). Long-term breast cancer-specific survival analyses by intra-tumor heterogeneity of ER were performed using Kaplan-Meier and multivariable Cox proportional hazard modeling adjusting for patient and tumor characteristics. Results: A statistically significant difference in long-term survival by high vs low intratumor heterogeneity of ER was seen for all ER-positive patients ( P < .001) and for patients with luminal A subtype tumors ( P = .01). In multivariable analyses, patients with high intratumor heterogeneity of ER had a twofold increased long-term risk as compared with patients with low intratumor heterogeneity (ER-positive: hazard ratio [HR] = 1.98, 95% confidence interval [CI] = 1.31 to 3.00; luminal A subtype tumors: HR = 2.43, 95% CI = 1.18 to 4.99). Conclusions: Patients with high intratumor heterogeneity of ER had an increased long-term risk of fatal breast cancer. Interestingly, a similar long-term risk increase was seen in patients with luminal A subtype tumors. Our findings suggest that intratumor heterogeneity of ER is an independent long-term prognosticator with potential to change clinical management, especially for patients with luminal A tumors.